Model Pembimbingan PLP II Berbasis “Hamemayu Hayuning Bawono” dalam Pembentukan Karakter Nilai Pancasila - Wikan Sasmita; Agus Widodo; Etty Andyastuti; Nursalim Nursalim (Jurnal Civic Hukum, 2026)
The guidance for School Field Practice (PLP II) is still dominated by a focus on pedagogical technical aspects and has not yet optimally integrated character formation based on Pancasila values and local wisdom. This study aims to: (1) analyze the philosophical and theoretical foundations of the PLP II guidance model based on the philosophy of Hamemayu Hayuning Bawono; (2) describe the implementation of the model in the mentoring process of practice students; and (3) identify its impact on the formation of Pancasila value-based character. A qualitative approach with an intrinsic case study design was used. The research subjects consisted of supervising lecturers, mentor teachers, and PLP II practice students. Data were collected through in-depth interviews, participatory observation, and document analysis, and then analyzed using an interactive model (reduction, presentation, and conclusion drawing). The validity of the data was tested through triangulation and member checking. The results showed that the Hamemayu Hayuning Bawono-based mentoring model is implemented through five main stages, namely value orientation, practice contextualization, reflective supervision, social collaboration, and character evaluation. This model has been proven to be able to comprehensively shape students' character, covering religiosity, nationalism, integrity, mutual cooperation, responsibility, democracy, social justice, and critical reasoning. The research conclusion shows that the integration of local wisdom in PLP II mentoring is effective in strengthening the internalization of Pancasila values in a reflective, contextual, and sustainable manner. This model can be an innovative alternative in the development of teacher professional education that is oriented towards character formation based on culture.